Integrated 1D-2D Resistivity Inversion for Mapping Seawater Intrusion in a Coastal Aquifer: Kenjeran-Surabaya, Indonesia Case Study - Himatul Farichah; Bagas Aryaseta; Aulia Dewi Fatikasari; Dini Oktavia (Advance Sustainable Science Engineering and Technology, 2026)
This study investigates the extent of intrusion in the Kenjeran coastal aquifer, Surabaya, Indonesia, through an integrated geophysical approach. Four one-dimensional Vertical Electrical Sounding (VES) surveys and two two-dimensional Electrical Resistivity Tomography (ERT) transects were conducted using Schlumberger and Wenner–Schlumberger configurations to obtain both depth-specific and laterally continuous resistivity data. The 1D VES results detected low-resistivity layers (<1.0 Ω·m) at depths exceeding 58–66 m, indicating deep saline groundwater. The 2D ERT sections identified wedge-shaped low-resistivity anomalies (0.1–0.8 Ω·m) at depths of 7.5 m to 48 m, indicating active intrusion progressing inland. Intrusion is more severe in the northern sector, with vertical penetration up to 48 m and horizontal encroachment beyond 200 m from the shoreline. The integration of 1D and 2D resistivity imaging proved effective in delineating saline–freshwater interfaces, enabling targeted mitigation measures and informed groundwater management to safeguard Kenjeran’s aquifer from further degradation.